The COVID-19 pandemic and student engagement in online learning: The moderating effect of technology self-efficacy - Yaw Owusu-Agyeman; Juliana Serwaa Andoh; Ernestina Lanidune (Journal of Pedagogical Research, 2021)
This study examines the moderating effect of technology self-efficacy on the relationship between online learning and student engagement in a higher education setting. A survey was used to gather data from participants (n=425) who were sampled from a population of registered students in a Technical University in Ghana. The data gathered were examined using hierarchical regression analysis. Results revealed that, technology self-efficacy strengthens 1) the positive relationship between online learning environment and student engagement; and 2) the positive relationship between instructional resources and student engagement. Secondly, the results revealed that the type of device used by students in the online learning environment has a positive and significant effect on student engagement. Conversely, findings of the current study show that while gender has a negative but significant effect on student engagement, age and academic discipline have insignificant effect on student engagement in the online learning setting. These findings among others lead the authors to propose ways that future studies could examine how technology self-efficacy, learning devices, instructional resources, institutional support systems and the online learning environment could be developed to enhance effective student engagement.